Holocene peatland initiation, lateral expansion, and carbon dynamics in the Zoige Basin of the eastern Tibetan Plateau. (September 2014) - Zhao, Yan; Tang, Yu; Yu, Zicheng; Li, Huan; Yang, Bao; Zhao, Wenwei; Li, Furong; Li, Quan
The Zoige Basin on the eastern Tibetan Plateau has the largest area of highland peatlands in China. However, the development history of these peatlands is still poorly understood. Understanding how these carbon-rich ecosystems responded to change in the Asian summer monsoons during the Holocene will provide insight into the peatland carbon accumulation processes under different climate boundary conditions. Here, we document the timing of initiation and expansion histories of these peatlands using 59 new basal peat ages across the Zoige Basin, with 29 ages for initiation analysis and 30 additional ages for lateral expansion analysis. Also, we synthesized basal ages from 26 sites and carbon accumulation records at four sites from previous studies in this region. The results show that the peatland initiation is widespread at 11.5–10 and 7–6 kyr (1 kyr = 1000 cal. yr BP) and the minimum initiation periods occurred after 5 kyr. Our multiple basal ages along eight transects show that slopes are a dominant control on peatland lateral expansion rates, with very slow and less variable rates at slopes >0.4°. Furthermore, we found a significant relationship between peatland basal ages and peat depths from 85 sites, suggesting relatively uniform peat properties. Carbon accumulation rates from detailed downcore analysis at four sites and on the basis of peat depth–basal age relationship show similar patterns with a peak carbon accumulation at 10–8 kyr. On the basis of estimated mean values of bulk density and carbon content from the region, the Holocene average C accumulation for the Zoige Basin is 31.1 g C/m 2 /yr. The widespread peatland initiation and rapid accumulation in the early Holocene were likely in response to higher temperature and stronger summer monsoon intensity, while the slowdown of peatland development during the late Holocene might have been caused by climate cooling and drying.